Economic Globalization, Political Economy and Investment Risks in Developing Countries - Atashgah, Marzyyeh (Journal of Global Economy, Business and Finance, 2024)
Background of the study: FDI, PFI, and BITs can facilitate foreign investors investing in developing countries to help economic development in the host country. However, in reality, developing countries have conditions that investors consider when making investment decisions. The aims and objectives: To identify investment risks in developing countries so that appropriate strategies are found to overcome these risks. Methods: The research carried out in this research is a library research method sourced from secondary sources. Results: Private foreign investors in developing countries face significant challenges, namely political instability, government policies, macroeconomic uncertainty, and acts of corruption from host countries. BITs provide vital legal certainty to create a safe and stable investment environment. Tax incentives benefit investors and host countries if solid and consistent laws regulate them. Conclusion: Foreign private investors face political instability, government policies, and corruption. BITs and tax incentives strengthen investment certainty.